Surface Interaction Model for Great Thickness Masonry - Sánchez, Ariel; González del Solar, Gerardo A.; Martín, Pablo E.; Maldonado, Noemi G. (Frontiers in Built Environment, 2017)
At present, many of the historic masonry structures in the most important seismic zone of Argentina present damages due to the actions to which they have been subjected. Therefore, it is necessary to study the behavior of walls of ceramic masonry of great thickness. This work presents the comparison between the results obtained from the numerical simulation of ceramic masonry walls subjected to compression and shear strength, through the use of interaction surfaces using commercial software ABAQUS, versus the data obtained from physical–mechanical tests performed in 1:1 scale on the laboratory of the CeReDeTeC. Tested walls were made of solid masonry bricks with cement and lime mortar of 26 and 45 cm thick, respectively. These were compared with the obtained results by the analysis software, considering mortar joints as interaction surfaces, trying to obtain the modeling that represents the behavior of the union of the elements mortar and masonry. The conclusions of the work detail the strengths and weaknesses of this type of masonry modeling and the desirability of developing models that allow to simulate the behavior of great thickness masonry.